Hepatic and Renal Failure after Anterior Myocardial Infarction Induced Apical Ventricular Septal Defect - Dirk Lossnitzer; Vedat Schwenger; Stephanie Lehrke; Evangelos Giannitsis; Martin Zeier; Hugo A. Katus; Henning Steen (Case Reports in Medicine)
We report the case of a 68-year-old man suffering from incremental hepatic and renal failure one month after anterior myocardial infarction. Cardiac MRI showed a pronounced apical post-AMI aneurysm, a moderate to severe mitral and tricuspid regurgitation as well as a hemodynamically highly significant 12 mm apical ventricular septal defect with a left-to-right ventricular shunt of almost 63% as the underlying cause. Heart X-ray revealed a severe LAD in-stent restenosis. CAPD catheter drainage of hydroperitoneum due to congestive liver and renal failure was provided in combination with intensified CAPD hemodialysis. Heart surgery was performed where the apical aneurysm was excised, the mitral valve was reconstructed, the IVSD was closed and the subtotally in-stent occluded LAD was bypassed. Post-surgery, the ascites were significantly reduced, and CAPD hemodialysis therapy could be terminated since the renal function gradually improved (MDRD = 25 mL/min). To our knowledge, for the first time we report successful CAPD catheter drainage of hydroperitoneum in combination with CAPD hemodialysis.